Corruption and Illegality in Asian Investment Arbitration. By Nobumichi Teramura, Luke Nottage, and Bruno Jetin (Eds). Springer 2024 - CARSON, Scatt (Journal of Economics Library, 2025)
This edited volume addresses the intersection of anti-corruption norms and international investment law, focusing specifically on how Asian jurisdictions and tribunals handle cases involving investor corruption and illegality. The book argues that, despite the increasing prominence of anti-corruption frameworks, a consistent regional approach to dealing with serious investor misconduct in Investor-State Dispute Settlement (ISDS) remains elusive, prompting this first-ever collection on the topic. Divided into three parts, the volume first provides an economic context, exploring the complex and often debated impact of corruption on Foreign Direct Investment (FDI) and economic growth in Asia. It then transitions to general legal issues, examining critical questions concerning the appropriate standard of proof for corruption claims, the impact of illegality on a tribunal’s jurisdiction or the merits of a claim, and the emergence of host-state counter-claims. The final section offers in-depth country reports on major Asian economies—including China, India, Indonesia, Japan, South Korea, and key Southeast Asian nations—to map the diversity of legal frameworks and arbitral experiences. Ultimately, the book proposes a roadmap for fostering a more harmonized and Asian-centric approach to address corruption and illegality in future investment agreements and arbitrations. Keywords. Investment Arbitration; Investor-State Dispute Settlement (ISDS); Transnational Corruption; Foreign Direct Investment (FDI); International Investment Agreements (IIA). JEL. K42; F21; D73; K33; F50.